Coronavirus Disease 2019 Disease Severity in Children Infected With the Omicron Variant . (11th April 2022) - Butt, Adeel A; Dargham, Soha R; Loka, Srusvin; Shaik, Riyazuddin M; Chemaitelly, Hiam; Tang, Patrick; Hasan, Mohammad R; Coyle, Peter V; Yassine, Hadi M; Al-Khatib, Hebah A; Smatti, Maria K; Kaleeckal, Anvar H; et al.
Abstract: Short Summary: Severe acute respiratory syndrome coronavirus 2 infection from the Omicron variant in children/adolescents is less severe than infection from the Delta variant. Those 6 to <18 years also have less severe disease than those <6 years old. Background: There are limited data assessing coronavirus 2019 (COVID-19) disease severity in children/adolescents infected with the Omicron variant. Methods: We identified children and adolescents <18 years of age with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with Delta and propensity score–matched controls with Omicron variant infection from the National COVID-19 Database in Qatar. Primary outcome was disease severity, determined by hospital admission, admission to the intensive care unit (ICU), or mechanical ventilation within 14 days of diagnosis, or death within 28 days. Results: Among 1735 cases with Delta variant infection between 1 June and 6 November 2021, and 32 635 cases with Omicron variant infection between 1 January and 15 January 2022, who did not have prior infection and were not vaccinated, we identified 985 propensity score–matched pairs. Among those who were Delta infected, 84.2% had mild, 15.7% had moderate, and 0.1% had severe/critical disease. Among those who were Omicron infected, 97.8% had mild, 2.2% had moderate, and none had severe/critical disease ( P < .001). Omicron variant infection (vs Delta) was associated with significantly lower odds of moderate or severe/critical disease (adjusted odds ratio [AOR], 0.12; 95% confidence interval [CI], .07–.18). Those aged 6–11 and 12 to <18 years had lower odds of developing moderate or severe/critical disease compared with those younger than age 6 years (aOR, 0.47; 95% CI, .33–.66 for 6–11 year olds; aOR, 0.45; 95% CI, .21–.94 for 12 to <18 year olds). Conclusions: Omicron variant infection in children/adolescents is associated with less severe disease than Delta variant infection as measured by hospitalization rates and need for ICU care or mechanical ventilation. Those 6 to <18 years of age also have less severe disease than those <6 years old.